Prevalence and detection of vibrio cholerae in fruit juices and flavored drinks. - Anyi, Ubong (2011)
This research was conducted to study the prevalence of V. cholerae in fruit juices and flavored drinks in Serdang, Selangor, Malaysia. Most probable number (MPN) method and Polymerase Chain Reaction (PCR) assay were combined together in this research to determine the prevalence and number of Vibrio spp. and V. cholerae in fruit juices and flavored drinks. None of the isolates were belong to the O1 and O139 serogroups. Vibrio cholerae isolates obtained from the drink samples were assessed for their antibiotic resistance characteristic and Randomly Amplified Polymorphic DNA (RAPD) profile. A survival study of V. cholerae O1 in carrot juice were carried out to provide the data on its survival in cold temperature at different incubation time interval. The total prevalence of Vibrio spp. in drink samples from hawker stalls was 93.3%. Vibrio spp. was most predominant in iced milk rose syrup, iced milk corn syrup and iced carrot milk, each at 100% prevalence. In restaurants, the total prevalence of Vibrio spp.was 93.3%, showing highest detection in iced milk rose syrup, iced apple juice and iced carrot milk. The prevalence of Vibrio spp. in iced milk rose syrup and iced carrot milk was 100%, while iced apple juice was 81.8%. The total prevalence of V. cholerae in drink samples from hawker stalls was 36.7 %. V. cholerae was most predominant in iced apple juice with 53.3% prevalence. In restaurants, the total prevalence of V. cholerae was 20%, showing highest detection in iced carrot milk, which is 27.8% prevalence percentage. The analysis of 120 drink samples showed that the concentration of Vibrio spp. ranged from <3 MPN/g to >2400 MPN/g while the concentration for V. cholerae ranged from <3 MPN/g to 2400 MPN/g. Thirty-eight V. cholerae isolates that were obtained by plating method were confirmed by PCR. During screening for O1 and O139, none of the isolates belong to this serogroups which are the main causative agent of cholera. Isolates obtained were subjected to Antibiotic Resistance Test. The tested isolates showed multi-resistance to as many as 11 antibiotics tested, with 97.3% resistant to erythromycin while majority were sensitive to ciprofloaxacin. RAPD-PCR profiles suggested that some of isolates that originated from different sources and locations were genotypically closely related. It has been reported that V. cholerae O1 has the ability to survive in cold temperature. Hence, the survival study of V. cholerae O1 in iced carrot juice was conducted. The survival study showed that V. cholerae O1 were unable to survive extreme temperature especially after a long incubation time. Vibrio cholerae O1 only showed growth at the beginning of incubation (0 hour), however, showed no growth after the 1st hour to the 6th hour of incubation.